2018
DOI: 10.1038/s41388-018-0268-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of BCL-XL and MCL-1 is required to induce tumour regression in lung squamous cell carcinomas sensitive to FGFR inhibition

Abstract: Genetic alterations in the fibroblast growth factor receptors (FGFRs) have been described in multiple solid tumours including bladder cancer, head and neck and lung squamous cell carcinoma (SqCC). However, recent clinical trials showed limited efficacy of FGFR-targeted therapy in lung SqCC, suggesting combination therapy may be necessary to improve patient outcomes. Here we demonstrate that FGFR therapy primes SqCC for cell death by increasing the expression of the pro-apoptotic protein BIM. We therefore hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…Taken together, LNCaP and C4‐2 cells demonstrated the greatest responses to single‐agent ABT‐263, but not ABT‐199, suggesting these cell lines are dependent on BCL‐xL for survival. Furthermore, our data reveal that baseline expression of BCL‐2, BCL‐xL or MCL‐1 were not predictive of sensitivity to the BH3‐mimetics tested, similar to studies in hematological malignancies and solid tumors …”
Section: Resultsmentioning
confidence: 99%
“…Taken together, LNCaP and C4‐2 cells demonstrated the greatest responses to single‐agent ABT‐263, but not ABT‐199, suggesting these cell lines are dependent on BCL‐xL for survival. Furthermore, our data reveal that baseline expression of BCL‐2, BCL‐xL or MCL‐1 were not predictive of sensitivity to the BH3‐mimetics tested, similar to studies in hematological malignancies and solid tumors …”
Section: Resultsmentioning
confidence: 99%
“…Combining two or even more BH3-mimetic drugs to inhibit several pro-survival BCL-2 proteins, either simultaneously or sequentially, may be an attractive approach to cancer therapy Khaw et al, 2016;Moujalled et al, 2018;Ramsey et al, 2018;Teh et al, 2018). However, it will be important to ensure that such strategies will not cause unacceptable on-target side effects, since combination targeting of MCL-1 and BCL-XL was reported to be lethal in mouse models, due to acute liver toxicity (Weeden et al, 2018). However, careful dosing and timing of drug administration may still make it possible to establish a therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase inhibition increases expression of pro-apoptotic BH3-only proteins, such as BIM and PUMA, thereby inhibiting pro-survival BCL-2 proteins that are not targeted by the BH3-mimetics (Cragg et al, 2007(Cragg et al, , 2008Rohrbeck et al, 2016). Accordingly, combinations of MCL-1 inhibitors, such as S63845 and AMG 176 (and the related compound AM 8621), with inhibitors of EGFR, MEK, or B-RAF were shown to efficiently diminish the in vitro and even the in vivo growth of cell lines derived from NSCLC (Kotschy et al, 2016;Leverson et al, 2015b;Nangia et al, 2018;Song et al, 2005;Zhang et al, 2011), lung squamous cell carcinoma (Weeden et al, 2018), hepatocarcinoma, or glioblastoma (Karpel-Massler et al, 2017). Of note, $85% of ER-positive breast cancers express high levels of BCL-2 (Dawson et al, 2010) and, accordingly, venetoclax and navitoclax synergized with tamoxifen in inhibiting the growth of patient-derived xenografts in mice (Vaillant et al, 2013).…”
Section: Impact Of Combinations Of Bh3-mimetics With Standard-of-carementioning
confidence: 99%
“…Very little is known about the relative role of Bcl-2/Bcl-XL/ Mcl-1 in other solid malignancies with FGFR1-3 activation. Recently, a study in lung cancer cell lines and PDX models showed that combining BGJ398 with either the Bcl-XL inhibitor A1331852 or the Mcl-1 inhibitor S63845 led to a small survival benefit and that only triple inhibition resulted in tumour regression (Weeden et al, 2018). The reason for the disparate results between lung and endometrial cancer models is unknown but could be due to higher expression of Mcl-1 in lung cancers and/or differences in other prosurvival/pro-apoptotic proteins regulated by FGFR1 and FGFR2.…”
Section: Discussionmentioning
confidence: 99%